2017
DOI: 10.3389/fmicb.2017.00272
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity Effect of Capsaicin in Mice Fed with High-Fat Diet Is Associated with an Increase in Population of the Gut Bacterium Akkermansia muciniphila

Abstract: Capsaicin (CAP) reduces body weight mainly through activation of transient receptor potential vanilloid 1 (TRPV1) cation channel. However, recent evidence indicates that the gut microbiota influences many physiological processes in host and might provoke obesity. This study determined whether the anti-obesity effect of CAP is related to the changes in gut microbiota. C57BL/6 mice were fed either with high-fat diet (HFD) or HFD with CAP (HFD-CAP) for 9 weeks. We observed a significantly reduced weight gain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 47 publications
1
84
1
3
Order By: Relevance
“…Moreover, a butter fat-based diet supplemented with California table grape powder can reduce obesity and hepatic lipogenesis in mice, associated with an increase in A. muciniphila in the gut (Baldwin et al, 2016). A higher abundance of A. muciniphila caused by the anti-obesity effects of Capsaicin also induces the increased expression of anti-microbial protein Reg3g and Mucin 2 protein in the gut (Shen et al, 2017). Compared with healthy patients, metformin promoted the abundance of A. muciniphila in diabetic patients.…”
Section: Nutritional and Medicinal Approches For Modulation Of Akkermmentioning
confidence: 99%
“…Moreover, a butter fat-based diet supplemented with California table grape powder can reduce obesity and hepatic lipogenesis in mice, associated with an increase in A. muciniphila in the gut (Baldwin et al, 2016). A higher abundance of A. muciniphila caused by the anti-obesity effects of Capsaicin also induces the increased expression of anti-microbial protein Reg3g and Mucin 2 protein in the gut (Shen et al, 2017). Compared with healthy patients, metformin promoted the abundance of A. muciniphila in diabetic patients.…”
Section: Nutritional and Medicinal Approches For Modulation Of Akkermmentioning
confidence: 99%
“…We performed two independent experiments. In the first experiment, wild type BALB/cJ mice (n = 36) were randomly divided into 6 groups of six animals, including normal mice group rRNA gene sequencing was performed following procedures described by Shen et al 9 Data are presented as the mean ± SEM, and statistical comparisons among the treatment groups were performed with the use of one-way ANOVA test followed by the nonparametric Tukey test, whereas the abundance of bacterial genes was compared using Student's t test (SPSS software package). Detailed methodology is provided in Supporting informations.…”
mentioning
confidence: 99%
“…TRPV1 is reported to be expressed primarily in the sensory neurons innervating most of the organs, including gastrointestinal tract (Holzer, 2011). Studies have shown that oral administration of capsaicin induced beneficial effects in obesity, such as increase in energy expenditure and browning in white adipose tissues, decreased lipid accumulation, and also improvement in gut dysbiosis conditions and changes in bacterial metabolites composition (Baboota et al, 2014; Shen et al, 2017; Wang et al, 2020). One of the important findings was increase in abundance of Akkermansia muciniphila , a mucin-feeding bacterium, which has been shown to improve overall microbial profile in gut (Baboota et al, 2014; Shen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that oral administration of capsaicin induced beneficial effects in obesity, such as increase in energy expenditure and browning in white adipose tissues, decreased lipid accumulation, and also improvement in gut dysbiosis conditions and changes in bacterial metabolites composition (Baboota et al, 2014; Shen et al, 2017; Wang et al, 2020). One of the important findings was increase in abundance of Akkermansia muciniphila , a mucin-feeding bacterium, which has been shown to improve overall microbial profile in gut (Baboota et al, 2014; Shen et al, 2017). As mucus layer deterioration has been associated with high-fat diet induced gut derangements (Birchenough et al, 2017; Everard et al, 2013), and the literature also shows a connection between capsaicin administration, TRPV1 and increase in expression of major mucins like MUC2, MUC5AC (Kang et al, 1995; Yang et al, 2013), we hypothesized that the effects of capsaicin in gut might be TRPV1-mediated and related to improved mucus secretion..…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation